PENGARUH INFLASI TERHADAP TINGKAT PENGANGGURAN DI INDONESIA PADA BULAN FEBRUARI PERIODE 2021-2024 - Mochamad Guntur; Muhammad Fikri Yusuf; Nadila Berlian Agustina; Luria Zahra; Arif Fadilla (Politeknik Bisnis Indonesia, 2024)
Inflation and unemployment are major problems that occur in all developing countries, including Indonesia. Inflation generally has both positive and negative impacts, depending on how severe it is. Mild inflation can improve the economy by encouraging people to work, save and invest. Since the beginning, one of the problems that will have negative consequences if inflation and unemployment are not controlled is the social, economic, political, cultural, and environmental fields. The purpose of this article is to measure how much inflation rate significantly affects the unemployment rate. This article uses a qualitative approach method in descriptive research. This research aims to evaluate the value of a variable independently without making comparisons with other variables. The results obtained are, the inflation rate in 2021 - 2024 has increased, on the contrary, the unemployment rate has decreased, which means that the inflation rate which is still quite under control does not cause an increase in the unemployment rate in Indonesia or inflation and the unemployment rate have a negative relationship.